Managing Tensions Between Evaluation and Research: Illustrative Cases of Developmental Evaluation in the Context of Research. (March 2014) - Rey, Lynda; Tremblay, Marie-Claude; Brousselle, Astrid
Developmental evaluation (DE), essentially conceptualized by Patton over the past 30 years, is a promising evaluative approach intended to support social innovation and the deployment of complex interventions. Its use is often justified by the complex nature of the interventions being evaluated and the need to produce useful results in real time. Despite its potential advantages, DE appears not to have been very widely used in research. The authors of this article decided to use this emergent approach in two evaluative research projects in health promotion. This article, coming out of their experiences, aims to assess the appropriateness of DE in research and describes issues related to its use. First, DE is presented, along with the potential advantages of its use in research. This is followed by a discussion of tensions related its application encountered in two studies carried out by the authors. The key issues are related to the links between academic and evaluative objectives, the dual role of researcher and consultant, and the temporality of the process. Finally, weighing the advantages of DE against its challenges, the authors conclude with a diagnosis regarding the application of this approach in research.